Accuracy of Cone Beam Computed Tomography for Detection of Bone Loss - Daryoush Goodarzi Pour; Elham Romoozi; Yadollah Soleimani Shayesteh (Tehran University of Medical Sciences, 2016)
Objectives: Bone assessment is essential for diagnosis, treatment planning and prediction of prognosis of periodontal diseases. However, two-dimensional radiographic techniques have multiple limitations, mainly addressed by the introduction of three-dimensional imaging techniques such as cone beam computed tomography (CBCT). This study aimed to assess the accuracy of CBCT for detection of marginal bone loss in patients receiving dental implants. Materials and Methods: A study of diagnostic test accuracy was designed and 38 teeth from candidates for dental implant treatment were selected. On CBCT scans, the amount of bone resorption in the buccal, lingual/palatal, mesial and distal surfaces was determined by measuring the distance from the cementoenamel junction to the alveolar crest (normal group: 0-1.5mm, mild bone loss: 1.6-3mm, moderate bone loss: 3.1-4.5mm and severe bone loss: >4.5mm). During the surgical phase, bone loss was measured at the same sites using a periodontal probe. The values were then compared by McNemar's test. Results: In the buccal, lingual/palatal, mesial and distal surfaces, no significant difference was observed between the values obtained using CBCT and the surgical method. The correlation between CBCT and surgical method was mainly based on the estimation of the degree of bone resorption. CBCT was capable of showing various levels of resorption in all surfaces with high sensitivity, specificity, positive predictive value and negative predictive value compared to the surgical method. Conclusion: CBCT enables accurate measurement of bone loss comparable to surgical exploration and can be used for diagnosis of bone defects in periodontal diseases in clinical settings.